Family, Teacher, and Peer-Support for the Dental Health Behavior among School-Age Children in Kwanyar Sub-District - Ach. Arfan Adinata; Nursalam Nursalam; Mira Triharini (International Journal of Nursing and Health Services (IJNHS), 2020)
Oral and dental health is an integral part of overall body health and is common in school children. Support from family, teachers, and peers plays an essential role in the dental health behavior of school-age children. This study aims to identify the relationship between interpersonal support and the behavior of elementary school students in maintaining dental health in Kwanyar District, Bangkalan Regency. Samples in the study of 150 grade 5 primary school students in Kwanyar Sub-District, Bangkalan Regency were obtained using Simple Random Sampling. The independent variable is interpersonal support, and the dependent variable is student behavior in maintaining dental health. The time of the study began April 08th - May 11th, 2019. The results of the study showed that family support was mostly in the good category, 71.3%. Teacher support is mainly in the good category 62.7% and friend support mainly in the less group 51.3%. The behavior of students in maintaining dental health is mainly in the good category 66.0%. The statistical test used is the Chi-Square test using SPSS 16.0. Chi-square test results were obtained on family support p-value 0.001 (<0.05), on teacher support p-value 0.032 (<0.05) and peer support value 0.804 (> 0.05). It means there is a relationship between family support and teachers with behavior in the Kwanyar District of Bangkalan District Work Area in 2019, while peer support has no ties. Conclusion: Interpersonal support, which includes family support and teachers, has an important role in shaping the behavior of school-age children and maintaining dental health. Parental and teacher support helps children in facing obstacles in maintaining dental health